REŞAT NURİ GÜNTEKİN'İN ROMANLARINDA YAPI VE İZLEK - KANTER, MUHAMMET FATİH (Fırat Üniveristesi, 2008)
Reşat Nuri Güntekin, Cumhuriyet dönemi Türk edebiyatında yazdığı eserleriyle önemli bir yer edinir. Bu çalışmada özellikle hikâye, tiyatro ve romanlarıyla bilinen yazarın romancılığı ele alındı.Çalışma üç bölümden oluşmaktadır. ?Monografi? niteliği taşıyan ilk bölümde yazarın yaşamı, edebi kişiliği ve eserleri hakkında bilgiler verildi.Çalışmanın temelini oluşturan ikinci bölümde Reşat Nuri Güntekin'in roman türündeki 19 eserini yapı ve izlek bakımından ayrı ayrı inceledik. Romanların yapısal ve izleksel kurgusunu incelerken roman teorisinin yanı sıra tarih, sosyoloji, felsefe ve psikoloji gibi bilim dallarından yararlandık. Böylece romanların yazıldığı tarihten günümüze geliş sürecindeki okunma ve algılanma biçimleri de gözler önüne serildi. Reşat Nuri'nin romanlarında yabancılaşma, kendini gerçekleştirme, aşk, narsisizm gibi bireysel sorunlar ve sömürü, yozlaşma, sosyal adaletsizlik gibi toplumsal sorunları izleksel açıdan değerlendirmeye çalıştık.Üçüncü bölümde, Reşat Nuri Güntekin'in romanlarında dil ve üslubun nasıl kullanıldığını sözcük ve cümle düzeyinde seçtiğimiz örneklerle inceledik.Reşat Nuri Güntekin romancılığının hangi aşamalardan geçtiğini belirleyen bir sonuç kısmından sonra, hem yazarla hem de alanla ilgili geniş bir kaynakça kısmına yer verdik.

Reşat Nuri Güntekin has been a notable person for his works written during the republican period of Turkish Literature. In this study, it has been dealt with the novelist side of the author who has been known with especially his stories, dramas and novels.This study consists of three parts. In the first part which has a monographic character, informative explanations about the life, literary character and works of the author have been given.In the second part which composes the basis of this study, we have analysed the 19 works of Reşat Nuri Güntekin which are in the form of novel, separately in terms of theme and structure.When analysing the structural and thematic formation of the novels, we have not only utilized from novel theory but other scientific branches such as history, sociology, philosophy and psychology as well. Thus, the way of being read and perceived of the novels within the period from the time of their being written to the present day has been displayed.We have tried to evaluate the individual matters such as alienation, self actualization, love, narcissism and the social problems like exploitation, degeneration, social injustice in the novels of Reşat Nuri from the thematic viewpoint.In the third part, we have searched the usage of the language and the style with the samples selected in the context of word and sentence.After a conclusion part determining the stages from which the novel writing (side) of Reşat Nuri have passed, we have allocated a wide place to the bibliography section related to both the field and the author.
Structure and theme in the novels of Reşat Nuri Güntekin
Keywords: Türk Dili ve Edebiyatı